2014
DOI: 10.1038/jid.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

UVA Irradiation of Human Skin Vasodilates Arterial Vasculature and Lowers Blood Pressure Independently of Nitric Oxide Synthase

Abstract: The incidence of hypertension and cardiovascular disease (CVD) correlates with latitude and rises in winter. The molecular basis for this remains obscure. As nitric oxide (NO) metabolites are abundant in human skin, we hypothesized that exposure to UVA may mobilize NO bioactivity into the circulation to exert beneficial cardiovascular effects independently of vitamin D. In 24 healthy volunteers, irradiation of the skin with two standard erythemal doses of UVA lowered blood pressure (BP), with concomitant decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
229
6
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 245 publications
(244 citation statements)
references
References 40 publications
4
229
6
5
Order By: Relevance
“…In contrast to our hypothesis and previous research (Mowbray et al, 2009, Oplander et al, 2009, Liu et al, 2014, exposure to UV-A light resulted in only a small, non-significant increase in plasma nitrite concentration compared to baseline. However, plasma nitrite declined from pre-to post-light exposure in the two SHAM trials (by 43 nM in PLA + SHAM and 69 nM in NIT + SHAM), a finding also reported by Liu and colleagues (2014).…”
Section: Effects Of Uv-a Light On Plasma Nitrite and Blood Pressurecontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our hypothesis and previous research (Mowbray et al, 2009, Oplander et al, 2009, Liu et al, 2014, exposure to UV-A light resulted in only a small, non-significant increase in plasma nitrite concentration compared to baseline. However, plasma nitrite declined from pre-to post-light exposure in the two SHAM trials (by 43 nM in PLA + SHAM and 69 nM in NIT + SHAM), a finding also reported by Liu and colleagues (2014).…”
Section: Effects Of Uv-a Light On Plasma Nitrite and Blood Pressurecontrasting
confidence: 99%
“…A Waldmann GH-8 ST unit (Herbert Waldmann, GmbH, Villingen-Schwenningen, Germany) containing eight, F851 100W UV-A bulbs (320-410nm; maximum 351 nm), was positioned 20 cm from the body. At this distance a dose of 20 J/cm 2 was produced which is the equivalent to two standard epithelial doses or 30 min exposure to sunlight at noon on a sunny day in Southern Europe (Liu et al, 2014). This dose of UV-A light has been shown to significantly increase plasma nitrite immediately after irradiation with values remaining elevated at least 40 min after exposure (Liu et al, 2014).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Although newer theories suggest that other components of sunlight (e.g. UVA non-vitamin D-making rays) might also have health effects, independent of vitamin D (33) . The association with disease incidence and latitude is not unique to IBD; there is supporting parallel evidence of a north-south gradient in the incidence of other autoimmune and gastrointestinal diseases, including rheumatoid arthritis (34) and colorectal cancer (35)(36)(37) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%